Nutrition Intervention Methods Based on Home-visit Nutritional Support and Verification of the Resulting Improvement Effects - Inoue, Keiko; Nakamura, Ikuko; Saito, Ikuko; Maeda, Kayoko; Maeda, Rei; Takasaki, Miyuki; anaka, Yayoi (Journal of the Japan Dietetic Association, 2012)
This study was conducted to study what kind of home-visit nutritional support (home-visit nutritional advice) should be conducted by registered dietitians in order to promote the application of nutritional support programs, and further to investigate how improvements could be obtained in the amount of nutrition intake in the elderly living at home and their general nutritional situation. The study included 62 cases of subjects receiving homevisit nutritional support (24 males, 38 females, age range 76 . 2±7 . 6 years old, nursing care level 3 . 0±1 . 6). The intervention was conducted from July through September of 2010, and the mini nutritional assessment (MNA®) was employed to access the nutrition, food intake volume, quality of life( QOL), and activities of daily living( ADL) of the subjects. A follow-up assessment was also conducted three months after the study was concluded. The MNA® results showed that 82% of the subjects were undernourished or at risk, and nine of the subjects dropped out of the study during the intervention due to being hospitalized, etc. It was apparent that the home-visit nutritional support should included advice related to a number of subjects, including weight management and eating snacks between meals, etc. The 53 subjects who concluded the intervention program showed a significant increase in the intake volume of nutritional elements, such as energy and protein, at the follow-up assessment conducted three months after the intervention program was concluded. In addition, body weight also showed a significant increase, and the MNA®, QOL, and ADL demonstrated significant improvements. Based on these results, it can be considered that registered dietitians can lay an important role in the improvement of nutrition, QOL, and ADL for elderly subjects living at home through the performance of a home-visit nutritional support intervention program.